The effects of diet form and feeder design on the growth performance and carcass characteristics of growing-finishing pigs - Myers, A.J.; Bergstrom, J.R.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,290 growing pigs (PIC 1050 × 337, initially 103.1 lb) were used in a 91-d study to evaluate the effects of diet form (meal vs. pellet) and feeder design (conventional dry vs wet-dry) on finisher pig performance. The treatments were arranged in a 2 × 2 factorial with 11 replications per treatment and 25 to 27 pigs per pen. Half of the pens were equipped with a 5-hole conventional dry feeder while the other half had a double-sided wet-dry feeder. All pigs were fed a corn-soybean meal-based diet containing 45 to 65% by-products in 4 phases. The only difference among treatments was diet form (meal vs. pellet). Pen weights and feed disappearance were measured on d 0, 16, 21, 43, 57, 71, and 91. Pictures of feeder pans were taken during Phase 4 and then evaluated by a panel of 4 for percentage of pan coverage. From d 0 to 91, no diet form × feeder design interactions were observed for ADG. Pigs fed pelleted diets had a tendency for improved (P < 0.07) ADG compared to those given meal diets. In addition, pigs fed with wet-dry feeders had improved (P < 0.01) ADG compared to those with conventional dry feeders. A diet form × feeder design interaction was observed (P < 0.04) for ADFI. When using a wet-dry feeder, pigs given meal diets had similar ADFI as those fed pelleted diets. However, when using dry feeders, pigs given pelleted diets had a much greater ADFI than pigs fed meal diets. In addition, a diet form × feeder design interaction was observed for F/G. Pigs fed both meal and pelleted diets via wet-dry feeders had similar F/G, but pigs fed pelleted diets in a conventional dry feeder had poorer F/G compared to pigs given meal diets in a conventional dry feeder. The pellets used during this experiment had average percentage fines of 35.1 ± 19% and an average pellet durability index (PDI) of 75.8 ± 8.4. We attribute the interactions to the poor pellet quality, leading to more feed wastage from the dry feeders. These results suggest that pellet quality is important to decrease feed wastage and sorting by the pigs and to optimize growth performance.
Keywords: Swine; Feeder; Feed processing; Pelleting